2014
DOI: 10.1159/000360946
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Virology of Hepatitis B Virus and Targets for Antiviral Intervention

Abstract: The members of the viral family Hepadnaviridae comprise one of the smallest enveloped DNA viruses and cause acute and chronic infections in mammals and birds, leading to large virus and antigen loads in the blood. They have a restricted host range and depend on differentiated hepatocytes for replication. Hepatitis B virus (HBV) is the prototype of the Hepadnaviridae. HBV can persist in infected hepatocytes and has evolved elaborate strategies to evade the immune system. HBV replicates like HIV (family of Retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 64 publications
0
14
0
2
Order By: Relevance
“…Hepatitis B virus (HBV) infection causes 70% of the viral hepatitis-related mortality [ 2 ]. Global estimates suggest that 3.6% of the world’s population is infected with HBV [ 3 ], with the highest burden in Asia and sub-Saharan Africa [ 4 , 5 ]. Human immunodeficiency virus (HIV) and HBV are significant public health threats in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) infection causes 70% of the viral hepatitis-related mortality [ 2 ]. Global estimates suggest that 3.6% of the world’s population is infected with HBV [ 3 ], with the highest burden in Asia and sub-Saharan Africa [ 4 , 5 ]. Human immunodeficiency virus (HIV) and HBV are significant public health threats in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Only one subject sample (1/14) returned a positive epitope ‘hit’ by peptide chip screening in the cyclic peptide chip, which comprised 15mer cyclic peptides from genotype A‐D. This reactivity was directed to the continuous cyclic epitope within the HBsAg L domain, residues 20‐32 (NPLGFFPDHQLDP), associated with the essential domain for NTCP receptor binding . The peptide screening also failed to identify any consistent continuous epitopes within the HBsAg, including the HBsAg S antigenic domain (HBsAg S residues 99‐169), which were the target of the anti‐HBs response developed post‐HBsAg clearance in this cohort of CHB functional cure patients.…”
Section: Resultsmentioning
confidence: 99%
“…One of the reasons is that HBV reverse transcription occurs after infection has been developed with formation of HBV cccDNA in the infected nuclei of hepatocytes, in contrast to HIV where reverse transcription occurs after the infection but before the integration of DNA into the host genome [88]. It is encouraging that it has recently been shown that with many years of NUC treatment (median period 126 months) there is marked depletion of cccDNA in the majority of patients, but it was also shown that although serum HBsAg levels were reduced, they remained detectable in 42 of 43 patients [89].…”
Section: Direct-acting Antiviralsmentioning
confidence: 99%